P27 as a Prognostic Factor of Early Cervical Carcinoma. Issue 1 (1st January 2013) - Bouda, Jiri; Hes, Ondrej; Koprivova, Miroslava; Pesek, Martin; Svoboda, Tomas; Boudova, Ludmila
Abstract : Objective: The aim of this study was to clarify whether the evaluation of cell-cycle regulatory protein p27 can serve as a prognostic factor in patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB cervical carcinoma. Patients and Methods: A retrospective study was performed on 130 surgically treated patients with FIGO stage IB cervical carcinoma with at least a 5-year follow-up. The expression of p27 was investigated independently by 2 experienced pathologists using immunohistochemistry. The prognostic significance of established prognostic factors and p27 expression were analyzed using univariate and multivariate analyses. Results: In a univariate analysis, lymph node status, tumor diameter, Gynecologic Oncology Group (GOG) score, lymph vascular space invasion, and p27 expression were significant prognostic factors for overall survival (OS). We found a correlation between p27 expression and lymph node status, tumor diameter, invasion, and GOG score. The p27 expression was a statistically significant prognostic factor for OS in a univariate analysis (log-rank test, P = 0.03). In a multivariate analysis, only lymph node status and tumor diameter were statistically significant prognostic factors for OS. Conclusions: This study demonstrated that a low p27 expression is associated with lymph node metastasis, deep stromal invasion, tumor diameter more than 20 mm, and high GOG score and had a prognostic influence on OS in a univariate analysis in a series of 130 women with FIGO stage IB cervical carcinoma. Lymph node status and the diameter of the tumor were the only statistically significant prognostic factors in multivariate analysis.